A theory of militant democracy the ethics of combatting political extremism - Kirshner, Alexander S. (Yale University Press, 2014)
"How should pro-democratic forces safeguard representative government from anti-democratic forces? By granting rights of participation to groups that do not share democratic values, democracies may endanger the very rights they have granted; but denying these rights may also undermine democratic values. Alexander Kirshner offers a set of principles for determining when one may reasonably refuse rights of participation, and he defends this theory through real-world examples, ranging from the far-right British Nationalist Party to Turkey's Islamist Welfare Party to America's Democratic Party during Reconstruction." -- Publisher's description.